2008
DOI: 10.2193/2007-025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Florida Key Deer Translocations

Abstract: The endangered Florida Key deer (Odocoileus virginianus clavium) is endemic to the Lower Florida Keys. In recent years, habitat fragmentation and restricted dispersal have resulted in small, isolated herds on some islands. Recovery biologists proposed translocations to increase the island herds that had declined or remained low; however, efficacy of Key deer translocations had yet to be evaluated. Our objective was to evaluate survival, ranges, reproduction, and dispersal of translocated deer. During 2003–2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Studies have shown that the decision to disperse or remain may depend on the release strategy, soft versus hard release (Carrie et al, 1996;Tuberville et al, 2005;Parker et al, 2008) although this may not apply to all species (Hardman & Moro, 2006), and all individuals in our study underwent an identical hard release. Dispersal may also depend on the perceived suitability of the new habitat (Bradley et al, 2005) but, although we did not assess variables of habitat quality, in this study, the release sites were essentially identical in vegetation and scrub cover as compared with the capture site habitat; in addition, the same main release site (11) was used both years.…”
Section: Discussionmentioning
confidence: 77%
“…Studies have shown that the decision to disperse or remain may depend on the release strategy, soft versus hard release (Carrie et al, 1996;Tuberville et al, 2005;Parker et al, 2008) although this may not apply to all species (Hardman & Moro, 2006), and all individuals in our study underwent an identical hard release. Dispersal may also depend on the perceived suitability of the new habitat (Bradley et al, 2005) but, although we did not assess variables of habitat quality, in this study, the release sites were essentially identical in vegetation and scrub cover as compared with the capture site habitat; in addition, the same main release site (11) was used both years.…”
Section: Discussionmentioning
confidence: 77%
“…The large (50 m perimeter) open-top cage situated at the release site provides an opportunity for the slow lorises to acclimatise to the new release environment and allows time to recover from the stress of transportation. This 'soft release' or 'delayed-release' technique has been found to influence success in translocations in other species (Bradley et al 2005, Parker et al 2008, but not in all cases (Hardman & Moro 2006), and suggests that certain successful techniques are often species or site specific.…”
Section: Discussionmentioning
confidence: 95%
“…However, for mammals, translocated Dormice ( Muscardinus avellanarius ) (Bright & Morris 1994), European Hares ( Lepus europaeus ) (Ferretti et al. 2010) and Florida Key Deer ( Odocoileus virginianus clavium ) (Parker et al. 2008) dispersed further than residents.…”
Section: Discussionmentioning
confidence: 99%
“…However, moving animals to unfamiliar surroundings may pose significant threats to translocated individuals, influencing the potential success of these conservation programmes. Faced with a novel environment, animals often exhibit significant increases in movements (Parker et al. 2008), apparently associated with unfamiliarity of the environment or searching for a suitable area to inhabit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation